Rentenir Sebagai Ancaman UMKM dan Solusi Komunikasi Risiko di Kelurahan Sukarasa - Aulya Nurulhikmah Hikmah; Anugrah Aulia Akbar; Muhamad Ariq Hakim; Eka Lestari; Kesya Gisela Jevinka; Muhammad Rizky Firdaus (Jurnal Penelitian Sosial Ilmu Komunikasi, 2025)
The increasing prevalence of loan shark practices among Micro, Small, and Medium Enterprises (MSMEs) in Sukarasa Subdistrict reflects a systemic vulnerability in financial risk management. This study aims to examine MSMEs’ motivations for relying on loan sharks, the socio-economic impacts they experience, and, more explicitly, how ineffective risk communication contributes to harmful financial decision-making. Using a qualitative case study approach, data were collected through in-depth interviews with MSME actors, community leaders, and subdistrict officials. The findings reveal that MSMEs’ dependence on loan sharks is not solely driven by urgent liquidity needs, but also by the absence of clear, accessible, and structured financial risk information. Formal institutions fail to deliver risk messages effectively, while loan sharks utilize persuasive interpersonal communication to create trust and normalize high-risk borrowing. As a result, MSMEs underestimate the dangers of high-interest lending, minimize coercive collection practices, and fall into prolonged debt cycles. This study emphasizes that strengthening financial literacy alone is insufficient; developing a participatory, context-based risk communication model is essential to enable MSMEs to recognize threats, evaluate lending alternatives, and make safer and more sustainable financial choices.